Improving Nutritional Status in Chronic Heart Failure Patients: Effectiveness of a Transtheoretical Model-Based Stepwise Nutritional Management Program - Yuan D; Xue Y; Zhou Y (Risk Management and Healthcare Policy, 2025)
Dejing Yuan,* Yuan Xue,* Yuefei Zhou Department of Nursing, the First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuefei Zhou, Email duduzhouyuefei@163.comObjective: To explore the nutritional status of chronic heart failure (CHF) patients and evaluate the effect of a transtheoretical model-based stepwise nutritional management program on nutritional improvement.Methods: This study conducted a retrospective analysis of 100 chronic heart failure (CHF) patients admitted to our hospital from March 2023 to May 2024. After applying inclusion and exclusion criteria, the patients were divided into an observation group and a control group. The observation group received a stepwise nutritional management program based on the transtheoretical model (TTM), while the control group received routine care. Nutritional improvement and clinical effects were compared between the two groups.Results: Among the 100 CHF patients, 27% had good nutritional status, 42% were at nutritional risk, and 31% had malnutrition. No significant differences in baseline data were found between the two groups (P > 0.05). After the intervention, the observation group showed significantly lower B-type natriuretic peptide (BNP) levels and higher left ventricular ejection fraction (LVEF) levels compared to the control group (P < 0.05). Psychological scores (Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS)) in the observation group were also significantly lower than those in the control group (P < 0.05). Additionally, serum total cholesterol (TC) and triglycerides (TG) levels were lower in the observation group (P < 0.05), and levels of prealbumin, transferrin, hemoglobin, and albumin were higher (P < 0.05). The Minnesota Living with Heart Failure Questionnaire (MLHFQ) scores in the observation group were significantly lower than in the control group (P < 0.05).Conclusion: The nutritional status of CHF patients is generally poor, and the transtheoretical model-based stepwise nutritional management program can effectively improve their nutritional status, enhance cardiac function, improve quality of life, and alleviate psychological burden. This intervention is promising for clinical practice.Keywords: chronic heart failure, nutritional status, transtheoretical model, stepwise nutritional management, quality of life